Strategies for the Construction of Supramolecular Dimers versus Homoleptic 1D Coordination Polymers Starting from the Diphosphorus [Cp2Mo2(CO)4(η2‐P2)] Complex and Silver(I) Salts. Issue 25 (6th July 2017) - Elsayed Moussa, Mehdi; Fleischmann, Martin; Peresypkina, Eugenia V.; Dütsch, Luis; Seidl, Michael; Balázs, Gabor; Scheer, Manfred
Abstract : The reactions of the tetrahedral diphosphorus [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] (1 ; Cp = C5 H5 ) complex with Ag[AlOC(CF3 )3 4 ] (AgTEF) (A ) and Ag[FAlOC(C6 F5 )(C6 F10 )3 ] (AgFAl) (B ) were studied. The first reaction led to the formation of the [Ag2 (η 2 ‐1 )2 (η 1 :η 1 ‐1 )2 ][TEF]2 (2 ) dimer and the [Ag2 (η 1 :η 1 ‐1 )3 ] n [TEF]2 n (3 ) coordination polymer, whereas the second reaction afforded the [Ag2 (η 1 :η 1 ‐1 )2 (η 1 ‐CH2 Cl2 )2 (η 2 ‐C7 H8 )2 ][FAl]2 (4 ) or the [Ag2 (η 2 ‐1 )2 (η 1 :η 1 ‐1 )2 ][FAl]2 (5 ) dimer and the [Ag2 (η 1 :η 1 ‐1 )4 ] n [FAl]2 n (6 ) coordination polymer. In each case, the products obtained depended on the ratio of the reactants and/or the synthetic procedure. Abstract : The reaction of the diphosphorus [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] (Cp = C5 H5 ) complex with Ag I salts allows the synthesis of dimers or 1D coordination polymers depending on the stoichiometry of the reactants used and the synthetic procedure.